Impact and indication of early systemic corticosteroids for very severe community-acquired pneumonia - Ugajin, Motoi (Dove Medical Press, 2013)
BACKGROUND: The efficacy of systemic corticosteroids in community-acquired pneumonia (CAP) has not yet been confirmed. We prospectively investigated the clinical features of patients treated with early adjunctive systemic corticosteroids and its clinical impact in very severe CAP. METHODS: One hundred and one consecutive CAP patients having a pneumonia severity index of >130 points were enrolled from August 2010 through February 2013. Early adjunctive systemic corticosteroids were defined as administration of systemic corticosteroids equivalent to prednisone of ≥20 mg/day added to initial antibiotics. The multivariate analysis was performed to evaluate the independent factors associated with mortality. RESULTS: Thirty-two patients (31.7%) died within 28 days of admission. Early adjunctive systemic corticosteroids were administered in 30 patients (29.7%), who more frequently had alteration of mental status, serious respiratory failure, or underlying lung diseases and received fluoroquinolones as initial antibiotics. In most patients treated with early adjunctive systemic corticosteroids, the dosage was less than 60 mg/day of an equivalent to prednisone by bolus intravenous infusion for a period shorter than 8 days. The occurrence of adverse events did not differ between the groups. Factors independently associated with mortality were blood urea nitrogen (hazard ratio [HR] 1.02, 95% confidence interval [CI] 1.00–1.04), serum albumin (HR 0.44, 95% CI 0.22–0.86), a requirement for intensive care (HR 4.93, 95% CI 1.75–13.87), and the therapy with early adjunctive systemic corticosteroids (HR 0.29, 95% CI 0.11–0.81). CONCLUSION: Early adjunctive systemic corticosteroids may have an effect to reduce the mortality in very severe CAP, although a larger-scale study is necessary.